2019
DOI: 10.1038/s41598-019-41857-z
|View full text |Cite
|
Sign up to set email alerts
|

Corrective saccades influence velocity judgments and interception

Abstract: In daily life we often interact with moving objects in tasks that involve analyzing visual motion, like catching a ball. To do so successfully we track objects with our gaze, using a combination of smooth pursuit and saccades. Previous work has shown that the occurrence and direction of corrective saccades leads to changes in the perceived velocity of moving objects. Here we investigate whether such changes lead to equivalent biases in interception. Participants had to track moving targets with their gaze, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
(58 reference statements)
2
35
1
Order By: Relevance
“…These early dynamic saccade-pursuit interactions support the current view of a tight coupling and shared information within the oculomotor system (Krauzlis, 2004;Orban de Xivry & Lefevre, 2007). Saccades and pursuit seem to be both driven by the same underlying position-and motion-related signals and also use a shared representation eye position and velocity (Orban de Xivry et al, 2006;Morris, Bremmer, & Krekelberg, 2016;Orban Deravet, Blohm, Orban de Xivry, & Lefèvre, 2018;Goettker et al, 2018;Goettker et al, 2019).…”
Section: Saccade-pursuit Interactionssupporting
confidence: 65%
See 1 more Smart Citation
“…These early dynamic saccade-pursuit interactions support the current view of a tight coupling and shared information within the oculomotor system (Krauzlis, 2004;Orban de Xivry & Lefevre, 2007). Saccades and pursuit seem to be both driven by the same underlying position-and motion-related signals and also use a shared representation eye position and velocity (Orban de Xivry et al, 2006;Morris, Bremmer, & Krekelberg, 2016;Orban Deravet, Blohm, Orban de Xivry, & Lefèvre, 2018;Goettker et al, 2018;Goettker et al, 2019).…”
Section: Saccade-pursuit Interactionssupporting
confidence: 65%
“…Consecutive saccadic and pursuit eye movements to the same target, such as in our study and the study of Bourrelly et al (2018b), could also be based on readouts of the same continuous signal, but with different integration time windows. An effect of different integration time windows was recently shown by Goettker, Brenner, Gegenfurtner, and de la Malla (2019). They found that interceptive hand movements were only affected by information roughly 100 ms before movement execution, but not by earlier information.…”
Section: Saccade-pursuit Interactionsmentioning
confidence: 83%
“…4A, inset). Such saccades will temporarily limit what one perceives (Bridgeman et al 1975;Burr et al 1999;Castet and Masson 2000;Maij et al 2012;Ross et al 2001;Zuber and Stark 1966) and give rise to errors in judging the target's position and motion (Goettker et al 2018(Goettker et al , 2019Honda 1989;Mateeff 1978;Matin and Pearce 1965;Maij et al 2009Maij et al , 2011Matziridi et al 2015;Morrone et al 1997;Schlag and Schlag-Rey 2002). If one knows where one will be able to hit the target in advance (imagine waiting for a fly to settle on a particular breadcrumb that it is clearly circling around; disk condition), it appears to be better to quickly direct one's gaze toward that position and track its approach with peripheral vision (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, observers initiate a smooth eye movement in the direction of the target's motion, especially if the target passes the initial fixation point after the time it usually takes to initiate a pursuit response (Rashbass, 1961). Moreover, although the primary role of catch-up saccades appears to be to realign gaze with the target of pursuit, such saccades do influence judgments of the target's speed and future position (Goettker, Brenner, Gegenfurtner, & de la Malla, 2019).…”
Section: Synergies Between Pursuit and Saccades In Predicting Object mentioning
confidence: 99%